COVIDOSE: A Phase II Clinical Trial of Low‐Dose Tocilizumab in the Treatment of Noncritical COVID‐19 Pneumonia. Issue 3 (10th December 2020) - Strohbehn, Garth W.; Heiss, Brian L.; Rouhani, Sherin J.; Trujillo, Jonathan A.; Yu, Jovian; Kacew, Alec J.; Higgs, Emily F.; Bloodworth, Jeffrey C.; Cabanov, Alexandra; Wright, Rachel C.; Koziol, Adriana K.; Weiss, Alexandra; et al.
Abstract : Interleukin‐6 (IL‐6)–mediated hyperinflammation may contribute to the mortality of coronavirus disease 2019 (COVID‐19). The IL‐6 receptor–blocking monoclonal antibody tocilizumab has been repurposed for COVID‐19, but prospective trials and dose‐finding studies in COVID‐19 have not yet fully reported. We conducted a single‐arm phase II trial of low‐dose tocilizumab in nonintubated hospitalized adult patients with COVID‐19, radiographic pulmonary infiltrate, fever, and C‐reactive protein (CRP) ≥ 40 mg/L. We hypothesized that doses significantly lower than the emerging standards of 400 mg or 8 mg/kg would resolve clinical and laboratory indicators of hyperinflammation. A dose range from 40 to 200 mg was evaluated, with allowance for one repeat dose at 24 to 48 hours. The primary objective was to assess the relationship of dose to fever resolution and CRP response. Thirty‐two patients received low‐dose tocilizumab, with the majority experiencing fever resolution (75%) and CRP decline consistent with IL‐6 pathway abrogation (86%) in the 24–48 hours following drug administration. There was no evidence of a relationship between dose and fever resolution or CRP decline over the dose range of 40–200 mg. Within the 28‐day follow‐up, 5 (16%) patients died. For patients who recovered, median time to clinical recovery was 3 days (interquartile range, 2–5). Clinically presumed and/or cultured bacterial superinfections were reported in 5 (16%) patients. Low‐dose tocilizumab was associated with rapid improvement in clinical and laboratory measures of hyperinflammation in hospitalized patients with COVID‐19. Results of this trial provide rationale for a randomized, controlled trial of low‐dose tocilizumab in COVID‐19.